Using Social Networking Sites in Research: An Emerging Approach to Engaging With Young People Who Have a Parent With a Mental Illness and/or Substance Abuse Disorder - Grové, Christine (Frontiers in Psychiatry, 2019)
The challenges involved in engaging young people who have a parent with a mental illness in research and in programs is well documented. Social networking sites provide a potentially useful medium to include at-risk youth and their families by removing some accessibility barriers that may prevent engagement and connection with individuals who parent or family member have a mental illness. This paper examines how social networking sites can be used to recruit youth and/or their families and engage them in research. Applying a case study analysis, the implications of using social media as a tool for recruitment and data collection and the ethical considerations and limitations will be discussed. Results tentatively indicate that social networking sites may be an effective method to engage young people of parents with a mental illness. The study argues for more informed use of social platforms for the translation and dissemination of research and intervention prevention. Overall, this paper will contribute to public mental health practice through guidelines and policy about social media research with at-risk young people and their families.